Effects of adult thymectomy on the contact sensitivity skin reaction and the unresponsiveness caused by feeding contact sensitizing agents. - Perera, M A (1981)
Unresponsiveness was produced in mice by three feeds of high doses of oxazolone or picryl chloride. The mice were then sensitized and contact sensitivity assessed by ear swelling. Adult thymectomy prevented the unresponsiveness caused by feeding. In some but not all experiments adult thymectomy also increased the response to a single skin paint. This effect of thymectomy was apparent at 1 week and reached a plateau at 2-3 weeks. The effect of adult thymectomy, on unresponsiveness caused by feeding and its ability to increase the contact sensitivity skin reaction, was reversed by treatment with crude thymosin fraction V.